Investigating the causal relationship of lipid metabolism in polycystic ovary syndrome: a Mendelian randomization study on the regulatory role of 3-Hydroxybutyrate in gene expression - Xu, Jia; Li, Lan; Yang, Shuo; Li, Ping; He, Bing; Kuang, Ji-lin (Frontiers in Medicine, 2026)
IntroductionPolycystic ovary syndrome (PCOS) is a prevalent endocrine disorder affecting 5–18% of reproductive-aged women, characterized by menstrual irregularities, hyperandrogenism, and polycystic ovarian morphology. Beyond its endocrine manifestations, PCOS involves significant metabolic dysfunction, particularly in lipid homeostasis. Elevated triglyceride levels are closely linked to insulin resistance and cardiovascular risk, suggesting a central role for lipid dysregulation in PCOS pathogenesis. However, traditional observational studies struggle to establish causal relationships due to confounding factors and reverse causality.MethodsTo address these limitations, this study employed a two-sample Mendelian randomization (MR) design to assess the causal effects of lipid-related metabolites—specifically triglyceride-rich lipoprotein subclasses—on PCOS susceptibility. Furthermore, to elucidate potential biological mechanisms, we integrated the MR analysis with in vitro functional experiments, focusing on the role of ketone body metabolism and specifically 3-hydroxybutyrate (3-HB), a major circulating ketone body known to regulate gene expression via epigenetic modifications.ResultsOur analysis identified a causal contribution of lipid-related metabolites to PCOS. notably, we demonstrated that 3-HB plays a critical role in the development of PCOS. Mechanistic investigations revealed that 3-HB contributes to metabolic and hormonal dysregulation primarily through the modulation of HDAC3 activity, linking ketone body metabolism directly to the disease phenotype.ConclusionThis study provides robust causal evidence linking lipid metabolism and ketone bodies to PCOS, moving beyond descriptive associations. by uncovering the specific pathway involving 3-HB and HDAC3, we highlight a novel molecular mechanism underlying PCOS pathogenesis. These findings suggest that targeting the 3-HB/HDAC3 axis could offer new strategies for therapeutic intervention in managing PCOS-related metabolic dysfunction.